Energy Balance, Myostatin, and GILZ: Factors Regulating Adipocyte Differentiation in Belly and Bone. (21st November 2007) - Shi, Xingming; Hamrick, Mark; Isales, Carlos M.
Abstract : Peroxisome proliferator-activated receptor gamma (PPAR-γ ) belongs to the nuclear hormone receptor subfamily of transcription factors. PPARs are expressed in key target tissues such as liver, fat, and muscle and thus they play a major role in the regulation of energy balance. Because of PPAR-γ 's role in energy balance, signals originating from the gut (e.g., GIP), fat (e.g., leptin), muscle (e.g., myostatin), or bone (e.g., GILZ) can in turn modulate PPAR expression and/or function. Of the two PPAR-γ isoforms, PPAR-γ 2 is the key regulator of adipogenesis and also plays a role in bone development. Activation of this receptor favors adipocyte differentiation of mesenchymal stem cells, while inhibition of PPAR-γ 2 expression shifts the commitment towards the osteoblastogenic pathway. Clinically, activation of this receptor by antidiabetic agents of the thiazolidinedione class results in lower bone mass and increased fracture rates. We propose that inhibition of PPAR-γ 2 expression in mesenchymal stem cells by use of some of the hormones/factors mentioned above may be a useful therapeutic strategy to favor bone formation.